The Role of Digital Media in Raising Awareness of University Students about the Dangers of Rumors and Its Impact on National Reconciliation: A Field Study on Students of Media Faculties in Libyan Universities - Tawfeeq Mustafa Hamad Ajweeli; Miftah Awadh Ramadhan Masoud; Eisa Sulayman Adreessulayman (Journal of Scientific and Human Dimensions, 2026)
This study aims to explore the role of digital media in raising awareness among Libyan university students about the dangers of rumors and to examine its impact on supporting national reconciliation. The study focuses on students of media faculties in Libyan universities, including the Faculty of Media at the University of Benghazi, the Faculty of Media – Al-Marj Branch, the Media Department at Al-Marqab University, and the Faculty of Media and Communication at Ajdabiya University. The sub-objectives include assessing students’ awareness of digital rumors, analyzing the relationship between their use of digital media and their ability to verify information, evaluating the influence of digital media awareness on students’ attitudes toward tolerance and social cohesion, and exploring the role of digital media in supporting national reconciliation, along with providing practical recommendations to enhance media literacy. The study adopted a descriptive-analytical approach, which is suitable for describing students’ use of digital media, measuring their awareness of digital rumors, and analyzing its impact on their attitudes toward national reconciliation. Data were collected using an electronic questionnaire based on a Likert scale, with a stratified random sample of 384 students from the four media faculties to ensure proportional representation. The results indicate that students have a moderately high level of awareness regarding digital rumors and that frequent use of digital media enhances their skills in verifying news and reducing the impact of misinformation. Goal-oriented digital content and awareness campaigns significantly contributed to promoting values of tolerance and peaceful coexistence while increasing awareness of national reconciliation and correcting misconceptions related to it. The findings also highlighted the need to intensify digital awareness campaigns, integrate media literacy programs into university activities, establish university platforms for fact-checking, and strengthen cooperation between universities and media institutions. Key recommendations include: enhancing digital awareness campaigns, integrating media literacy programs into university curricula, promoting verification skills, supporting goal-oriented digital content, using digital media to advance national reconciliation, creating university-based fact-checking platforms, and fostering collaboration between universities and media organizations to enhance societal stability.